BERKAH Learning Model Design for Elementary School Curriculum Transformation: 21st Century Skills Development - Ana Ratnasari (Pedagogi: Jurnal Ilmu Pendidikan, 2026)
This study aims to develop the initial design of the BERKAH instructional model as a transformative pedagogical framework for implementing the Merdeka Curriculum in Indonesian primary schools. The BERKAH model an acronym for Critical Thinking (Berpikir Kritis), Empathy, Reflection, Collaboration, Adaptation, and Humanization, was conceptualized to meet the urgent need for a more holistic learning approach that integrates 21st-century competencies (6C) with humanistic and local values. Adopting a design and development research methodology based on the 4D model (Define, Design, Develop, Disseminate), this study focuses on the first two stages: Define and Design. Data were collected through surveys and interviews involving elementary school teachers who have implemented the Merdeka Curriculum. The findings highlight that while teachers recognize the importance of cognitive development, they face challenges in embedding affective and moral dimensions explicitly within classroom practices. The BERKAH model offers a context-responsive, values-oriented pedagogical design that complements and extends existing approaches such as Problem-Based Learning (PBL) and Project-Based Learning (PjBL), particularly by addressing their limitations in fostering empathy, reflection, and character formation. By aligning with the values of Profil Pelajar Pancasila, BERKAH as a meaningful instructional innovation for 21st-century learning